The “L-Sandwich” Strategy for True Coronary Bifurcation Lesions: A Randomized Clinical Trial - Quan Guo; Liang Peng; Lixin Rao; Cao Ma; Kang Zhao; Zhenzhou Zhao; Haiyu Tang; Muwei Li (Journal of Interventional Cardiology)
Background. This study explored the efficacy of the “L-sandwich” strategy, which involves the implantation of stents in the main vessel (MV) and shaft of the side branch (SB) with a drug-coated balloon (DCB) applied to the SB ostium, for coronary true bifurcation lesions. Methods and Results. Of 99 patients with true bifurcation lesions, 38 patients underwent the “L-sandwich” strategy (group A), 32 patients underwent a two-stent strategy (group B), and 29 patients underwent a single-stent + DCB strategy (group C). Angiography outcomes (late lumen loss [LLL], minimum lumen diameter [MLD]), and clinical outcomes (major adverse cardiac events [MACEs]) were analyzed. At 6 months, the MLD of the SB ostium in groups A and B were similar (P>0.05) and group A larger than group C (P<0.05). The LLL of group B was the largest among the three groups (P<0.05). The MLD of the SB shaft in groups A and B were larger than in group C (P<0.05). The LLL of the SB shaft in group C was the lowest (P<0.05). Two patients in group B received target vessel revascularization at the 6-month followup (P>0.05), and patients in the other groups had no MACEs. Conclusions. The “L-sandwich” strategy was feasible for the treatment of true coronary bifurcation lesions. It is a simpler procedure with similar acute lumen gain than the two-stent strategy, results in a larger SB lumen than the single-stent + DCB strategy, and it can also be used as a remedy for dissection following the single-stent + DCB strategy.